Activity of B-nor analogues of neurosteroids on the GABAA receptor in primary neuronal cultures - Suñol, Cristina (2006)
A GABAA receptor study of several B-nor analogues of allopregnanolone and pregnanolone has been carried out. B-Norallopregnanolone (i.e., 3α-hydroxy-7-nor-5α-pregnan-20-one) was found comparable to allopregnanolone when measured with labeled TBPS. Analogous results were obtained from their effect on neurons in culture: this time, both 3α-hydroxy-7-nor-5ξ-pregnan-20-ones (5 and 6) were found to stimulate [3H]flunitrazepam binding and GABA-induced 36Cl - influx. These effects were inhibited by GABAA receptor antagonists. Other analogues carrying electronegative substituents (epoxides 9 and 10 and ketone 12) in the B ring were inactive. Similarly, B-normal ketones 17, and 18 and 6-azasteroids 20 and 21 were also inactive. B-Nor analogues 5 and 6 did not induce neurotoxicity at relevant concentrations. A computational analysis of active and inactive neurosteroid analogues allowed the proposal of a 3D pharmacophoric hypothesis of their interaction with the GABAA receptor. © 2006 American Chemical Society.